Surgical removal of a fungus ball formed in the maxillary sinus secondary to surgically assisted rapid palatal expansion procedure during Le Fort I osteotomy - Sancar, Bahadir; Burak Duman, Suayip; Unluturk, Burak (Annals of Medical Research, 2021)
None
Keywords: Aspergillus; maxillary sinus; osteotomy